The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/2013gl057942
|View full text |Cite
|
Sign up to set email alerts
|

Elastic dynamics and tidal migration of grounding lines modify subglacial lubrication and melting

Abstract: [1] We combine the dynamics of ice, bed, and ocean in a new elastic model for the tidal-timescale migration of grounding lines on deformable foundations. Previous interpretations of tidal flexure using models of elastic ice shelves with fixed grounding lines were found to be inconsistent, suggesting an elasticity of ice that varies spatially and temporally and that is significantly smaller than measured experimentally. We argue here that with our model, a consistent, purely elastic interpretation can be made. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 30 publications
6
92
0
Order By: Relevance
“…The model does not take into account feedback between ice flexure and water pressure. water pressure and it has been suggested that this mechanism could pump brackish water upstream (Walker et al, 2013;Sayag and Worster, 2013). This flexure may have the additional effect of opening crevasses beneath the ice or dilating the subglacial till, leading to changes in local water storage and thereby altering the distribution of water.…”
Section: Discussionmentioning
confidence: 99%
“…The model does not take into account feedback between ice flexure and water pressure. water pressure and it has been suggested that this mechanism could pump brackish water upstream (Walker et al, 2013;Sayag and Worster, 2013). This flexure may have the additional effect of opening crevasses beneath the ice or dilating the subglacial till, leading to changes in local water storage and thereby altering the distribution of water.…”
Section: Discussionmentioning
confidence: 99%
“…, representing a relatively stiff bed (Sayag and Worster, 2013) to avoid complicating our results with soft till effects. At the GL ice is pinned to the bed such that the GL cannot migrate, in accordance with DInSAR analysis that shows no GL migration at this site (Wild and others, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Sayag and Worster (2013) explored this process using elastic beam theory and found that changes in overburden pressure of the ice over a tidal cycle could lead to a hydrological barrier that acts as a control on subglacial hydrology.…”
Section: Overview Of Previous Studiesmentioning
confidence: 99%